2009
DOI: 10.1179/14653120723166
|View full text |Cite
|
Sign up to set email alerts
|

Colour changes of orthodontic elastomeric module materials exposed toin vitrodietary media

Abstract: Clinicians should make patients aware of the effect of consuming beverages and spices on the colour stability of their selected ligature modules. Clinicians should favour modules made with injection moulding. Darker colour modules may be preferred to clear modules to avoid excessive colour degradation through dietary media such as beverages and food spices. Patients consuming large amounts of spices or coffee should avoid clear modules made by extrusion processing because of their tendency to discolour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
61
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(72 citation statements)
references
References 18 publications
8
61
2
1
Order By: Relevance
“…4 In assessing the color, laboratory investigations were performed in an attempt to find differences in the staining of these elastomeric ligatures after immersion in different solutions. In these investigations, the change in color was measured quantitatively by means of a visual analog scale 12 or computational analyses, 10,11 The results indicated that certain substances stain more than others, such as methylene blue and red pepper sauce. 10,11 Although a visually perceptible color change value was reported, 11 the equipment used in the research features considerable optical sensitivity and can be influenced by luminance and color of the surface on which the elastomeric ligatures are examined.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4 In assessing the color, laboratory investigations were performed in an attempt to find differences in the staining of these elastomeric ligatures after immersion in different solutions. In these investigations, the change in color was measured quantitatively by means of a visual analog scale 12 or computational analyses, 10,11 The results indicated that certain substances stain more than others, such as methylene blue and red pepper sauce. 10,11 Although a visually perceptible color change value was reported, 11 the equipment used in the research features considerable optical sensitivity and can be influenced by luminance and color of the surface on which the elastomeric ligatures are examined.…”
Section: Discussionmentioning
confidence: 99%
“…In these investigations, the change in color was measured quantitatively by means of a visual analog scale 12 or computational analyses, 10,11 The results indicated that certain substances stain more than others, such as methylene blue and red pepper sauce. 10,11 Although a visually perceptible color change value was reported, 11 the equipment used in the research features considerable optical sensitivity and can be influenced by luminance and color of the surface on which the elastomeric ligatures are examined. Furthermore, one cannot determine to what extent color variations can compromise the visual esthetic pleasantness of an elastomeric ligature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations